A non-destructive study of crack development during thermal cycling of Al wire bonds using x-ray computed tomography - Agyakwa, Pearl; Yang, Li; Corfield, Martin; Johnson, Christopher Mark (2014)
This paper concerns the non-destructive visualisation of the evolution of damage within ultrasonically bonded alumini-um wires using three dimensional x-ray computed tomography. We demonstrate the potential to observe the progressive accumulation of damage within the same wires during passive thermal cycling between -55°C and 190°C. Tomography datasets were obtained prior to and after cycling. Cracks could be seen emerging from the extreme ends of the bonds when imaged after 105 cycles. Subsequent cycling lead to the advancement of these cracks toward the centres of the bonds. In addition, damage developed within the interior of the bonds; these also grew with increase in number of cy¬cles, and merged with existing cracks. Virtual cross-sections have been analysed to quantify the rate of damage build up.